Climate change anxiety scale: psychometric validation among university students in environmental sustainability contexts - Bassam M. A. Makram; Mohamed Sayed Abdellatif; Ahmed Abdelhalim Elnhal; Mohamed Ali Nemt-allah (Institute of Advanced Engineering and Science, 2026)
This study employed a cross-sectional, two-sample validation design to develop and validate the climate change anxiety scale (CCAS) among Egyptian university students, addressing the critical gap in Arabic-language assessment tools for climate-related psychological distress. Two independent samples from Al-Azhar University participated: 540 students completed exploratory factor analysis (EFA) and 977 students completed confirmatory factor analysis (CFA). Content validity was established through expert review (content validity indices (CVI)=.778-1.000), resulting in an 18-item scale. EFA revealed a three-factor structure explaining 53.981% of variance: cognitive-emotional impairment, functional impairment, and behavioral engagement. CFA confirmed excellent model fit (comparative fit index (CFI)=.944, root mean square error of approximation (RMSEA)=.067), significantly superior to a single-factor model. Internal consistency was robust across subscales (ω=.817-.907, α=.813-.906) and total scale (ω=.910, α=.909). Test-retest reliability demonstrated strong temporal stability (r=.714-.886). Convergent validity was supported through significant inter-dimensional correlations (r=.394-.710). The CCAS provides a psychometrically sound, culturally appropriate instrument for assessing multidimensional climate anxiety, enabling systematic identification of students requiring targeted mental health interventions within Egyptian higher education contexts.